2018
DOI: 10.1177/1077558718781117
|View full text |Cite
|
Sign up to set email alerts
|

Accountable Care Organizations and Post-Acute Care: A Focus on Preferred SNF Networks

Abstract: Due to high magnitude and variation in spending on post-acute care, accountable care organizations (ACOs) are focusing on transforming management of hospital discharge through relationships with preferred skilled nursing facilities (SNFs). Using a mixed-methods design, we examined survey data from 366 respondents to the National Survey of ACOs along with 16 semi-structured interviews with ACOs who performed well on cost and quality measures. Survey data revealed that over half of ACOs had no formal relationshi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 17 publications
0
18
0
Order By: Relevance
“…Case studies and qualitative research indicate that ACOs have begun to implement changes to the discharge process and to manage post-acute care actively and have identified potential mechanisms through which changes may occur (37,38). In some cases, post-acute settings can act as substitutes for one another, though they have widely differing reimbursement rates.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…Case studies and qualitative research indicate that ACOs have begun to implement changes to the discharge process and to manage post-acute care actively and have identified potential mechanisms through which changes may occur (37,38). In some cases, post-acute settings can act as substitutes for one another, though they have widely differing reimbursement rates.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…Several policy and economic drivers suggest the need for better partnerships between acute care hospitals and nursing facilities. For example, concerns over reducing readmissions from nursing facilities and recognition of problems with transitions of care have prompted many health systems to develop closer relationships with post–acute care providers . Further, payment mechanisms, such as accountable care organizations and bundled payment programs, have incentivized some health systems to tighten connections with nursing facilities over the past several years.…”
mentioning
confidence: 99%
“…4 Increasing recognition of the significant cost and poor outcomes of postacute care led to payment reforms, such as bundled payments, that incentivized less expensive forms of postacute care and improvements in outcomes. [5][6][7][8][9] Early evaluations suggested that hospitals are sensitive to these reforms and responded by significantly decreasing SNF utilization. 10,11 It remains unclear whether this was safe and effective.…”
mentioning
confidence: 99%